Identidade negra e mediações da informação (étnico-racial) em blogs de funk - (:unkn) unknown (Instituto Brasileiro de Informação em Ciência e Tecnologia/Universidade Federal do Rio de Janeiro, 2019)
This thesis investigates the process of the construction of black identity, through the processes of mediation of information in funk blogs, establishing a comparison with online news portals. It works with a hypothesis that this information is configured as a medium that may contribute or inhibit to the (re)construction of black identity. It justifies the adherence of research in the field of Information Science and the state of the art of ethnic-racial relations and music in Brazilian research in Information Science. Underpinning the theoretical network, it dialogues with the Cultural Studies with the Intercultural Information Ethics. It also operates the concepts of black identity and racism, within a decolonial perspective, as well as mediation of information, to identify in the funk blogs a confluence between the two phenomena, from the occurrence of ethnic-racial information. In the methodological course is presented the Critical analysis of the discourse as an approach for the data analysis, interpreting the discourse as a social practice. It concludes by stating that funk blogs have the potential to produce a discourse that disseminates ethnic-racial information, thus being able to (re)construct a black identity that replaces negative and stereotyped images with positive images aimed at the empowerment of the black population, however, a reductionist view of funk when reported by the information portal, associating it mostly with crime contexts.
Keywords: Ciência da informação; Identidade negra; Blogs de funk; Ética intercultural da informação; Informação étnico-racial; Mediação da informação; Black identity; Funk Blogs; Intercultural Information Ethics; Ethnic-racial information; Mediation of information; Information Science; Ciência da informação